Ответы и объяснения

  • Участник Знаний
2013-10-01T21:36:24+04:00
Y = 0.5*(X^2 + 8X - 11) = 0
D = 64 - 4*1*(-11) = 64 + 44 = 108  
V D = V 108 = V 4 * 27 = 2 V 27 
X1 = ( - 8 + 2 V 27 ) 2 = 2*(-4 + V 27) \ 2 = ( - 4 + V 27)
X2 = ( 2 * ( - 4 - V 27 ) ) \ 2 = ( - 4 - V 27 )
Y = ( X + 4 - V 27 ) * ( X + 4 + V 27)
1) X + 4 - V 27 = 0 ---> X = ( - 4 + V 27)
2) X + 4 + V 27 = 0 --> X = ( - 4 - V 27)
-------------------------------------------------------->
- 4 - V 27                      - 4 + V 27
ответ: ( - 4 - V 27   ;   - 4 + V 27 )